STRATEGI NAFKAH RUMAH TANGGA NELAYAN TRADISIONAL DAN MODERN PADA KOMUNITAS NELAYAN SEKUNYIT, KAUR, PROVINSI BENGKULU - Yuliana, Lidia; Widiono, Septri; Cahyadinata, Indra (Jurnal AGRISEP, 2016)
This research aimed to explore the household adaptation of Sekunyit fishermen to the fisheries modernasation in terms of livelihood strategies as a strategy for survival. This research was conducted in the Sekunyit Village, South Kaur District, Kaur regency by using case studies of two traditional fishermen households and two modern fishermen households. It is found that livelihood strategies both of the traditional and modern fishermen includes a multiple sources income, the involvement of family members, and applying their social networks and out-migration as coping strategy. The livelihood strategies conducted in the context of three vulnerability namely the vulnerability of ecology, price system, and single fishery resource were run.